Financial stability instruments for the banking systems of Ukraine - Pogorelenko, Natalia (Social Economics, 2020)
The article focuses on the issues of systematization, analysis and development of the classification of instruments for ensuring the financial stability of the banking system, which is a determining factor in the formation of the necessary influences to ensure the financial stability of the banking system.For the selection and application of the toolkit that most precisely meets the goals, current conditions and priorities of ensuring the financial stability of the banking system, its classification was supplemented by the introduction of new classification features.In particular, in order to take into account the importance of maintaining the continuous circulation of financial flows in the banking system, their consistency and synchrony, we developed a classification criterion ‘for influencing the inflow and outflow of financial flows’, which makes it possible to use the appropriate instrument to complete such specific tasks as ensuring continuity, streamlining the cost of resources, smoothing the impact on interest rates of liquidity changes.Based on the presence of different levels of regulatory influences on ensuring the financial stability of the banking system – strategic and operational – the classification criteria ‘to influence the achievement of monetary policy operational goals’ and ‘to influence the achievement of strategic monetary policy goals’ were introduced.The classification criterion ‘impact on systemic/state-owned banks’ is justified by the significance of systemically important banks for ensuring the financial stability of the banking system, since a significant concentration of assets and capital in such banks requires the use of special tools aimed at preventing systemic risks.Taking into account the need for balancing the flows of credits provided by the banking system, the impact of risks on banking activities, the classification features of instruments for ensuring the financial stability of the banking system ‘by impact on the credit cycle’, ‘by key risks’, ‘by organizational elements’ were proposed.Allocation of the classification features of the instruments for ensuring the financial stability of the banking system will contribute to the achievement of targeting of regulatory and organizational influences and compliance with the criteria of rationality and adequacy when choosing specific instruments. This will create the basis for the selection and application of such a combination of instruments that most closely meets the goals, current conditions and priorities for ensuring the financial stability of the banking system.